Maternal and Child Expressed Emotion as Predictors of Treatment Response in Pediatric Obsessive–Compulsive Disorder - Przeworski, Amy (2012)
Expressed emotion (EE) is associated with symptoms and treatment outcome in various disorders. Few studies have examined EE in pediatric OCD and none of these has assessed the child’s perspective. This study examined the relationship among maternal and child EE, child OCD severity, and OCD-related functioning pre- and post-treatment. At pre-treatment, mothers completed speech samples about the child with OCD and an unaffected sibling. Children with OCD completed speech samples about parents. There were low rates of high maternal EE (child with OCD: 16.1%; sibling: 2.6%) and high child EE about parents (mothers: 11.9%; fathers: 10.2%). High EE was primarily characterized by high criticism, not high overinvolvement. High maternal EE and child EE regarding fathers were associated with pre-treatment child OCD severity but not post-treatment severity. High child and maternal EE were predictive of post-treatment OCD-related functioning. EE may be an important child and maternal trait associated with pre-treatment OCD severity and generalization of treatment gains.